The impact of plasma membrane lipid composition on flagella-mediated adhesion of enterohemorrhagic Escherichia coli - Cazzola, Hélène; Lemaire, Laurine; Acket, Sébastien; Prost, Elise; Duma, Luminita; Erhardt, Marc; Čechová, Petra; Trouillas, Patrick; Mohareb, Fady R.; Rossi, Claire; Rossez, Yannick (American Society for Microbiology, 2020)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 is a major cause of foodborne gastrointestinal illness. The adhesion of EHEC to host tissues is the first step enabling bacterial colonization. Adhesins such as fimbriae and flagella mediate this process. Here, we studied the interaction of the bacterial flagellum with the host cell’s plasma membrane using giant unilamellar vesicles (GUVs) as a biologically relevant model. Cultured cell lines contain many different molecular components, including proteins and glycoproteins. In contrast, with GUVs, we can characterize the bacterial mode of interaction solely with a defined lipid part of the cell membrane. Bacterial adhesion on GUVs was dependent on the presence of the flagellar filament and its motility. By testing different phospholipid head groups, the nature of the fatty acid chains, or the liposome curvature, we found that lipid packing is a key parameter to enable bacterial adhesion. Using HT-29 cells grown in the presence of polyunsaturated fatty acid (α-linolenic acid) or saturated fatty acid (palmitic acid), we found that α-linolenic acid reduced adhesion of wild-type EHEC but not of a nonflagellated mutant. Finally, our results reveal that the presence of flagella is advantageous for the bacteria to bind to lipid rafts. We speculate that polyunsaturated fatty acids prevent flagellar adhesion on membrane bilayers and play a clear role for optimal host colonization. Flagellum-mediated adhesion to plasma membranes has broad implications for host-pathogen interactions.
Keywords: adhesins; flagella; lipid rafts; phospholipids